Application of Rice Straw and Tithonia for Increasing Fertilizer Use Efficiency on Paddy Soil - Gusnidar, .; Yasin, Syafrimen; Burbey, .; Yulnafatmawita, .; Saleh, Sulaiman; Andhika, Rantau (JOURNAL OF TROPICAL SOILS, 2012)
The research was aimed to obtain a combination of rice straw (S) and tithonia (Tithonia diversifolia) (T) to increasechemical fertilizers use efficiency (FUE) on paddy soil which was conducted in Sicincin, Padang Pariaman Regencyin 2008. The experiment consisted of 8 treatments (A= recommendation input: 200 kg Urea ha-1 (Ru) + 100 kg SP-36ha-1 (Rp) + 75 kg KCl ha-1 (Rk)), B = Ru + 2Rp, C = 2.5 Mg Tithonia (T) ha-1 + 75% Ru+10 kg SP36 ha-1 as a starter Pfertilizer (P-s), D = T + 75% Ru, E = 5 Mg Rice Straw (S) ha-1 (Sr) + Ru + Rp + Rk, F = Sr + Ru + P-s, G = T + 0.5Sr + 75%Ru + P-s, H = T + 0.5S + 50% Ru + P-s) with three replications. The treatments were randomly allocated in each blockRandomized Block Design (RBD). The results showed that application of fresh organic matter (OM) from tithonia +75% recommended Urea without KCl and P-starter addition on intensification rice field increased synthetic FUE onpaddy soil. Application of tithonia for 2.5 Mg ha-1 + 75% of recommended Urea (150 kg Urea), without synthetic Pand K fertilizers seemed to be the best treatment to get the highest yield (8.08 Mg Harvested Dry Seed (HDS) ha-1(= 7.05 Mg Milled Dry Seed (MDS) ha-1) of rice, then it was followed by the treatment based on farmer tradition inputwith the yield was 7.25 Mg HDS ha-1 (= 6.41 Mg MDS ha-1). The use of fresh tithonia as much as 2.5 Mg ha-1 basedon its dry weight could be considered as an alternative fertilizer for rice crops in intensification rice field.[How to Cite: Gusnidar, S Yasin, Burbey, Yulnafatmawita, S Saleh and R Andhika. 2012. Application of Rice Straw and Tithonia for Increasing Fertilizer Use Efficiency on Paddy Soil. J Trop Soils 17 (2) : 151-156. Doi: 10.5400/jts.2012.17.2.151]Â [Permalink/DOI: www.dx.doi.org/10.5400/jts.2012.17.2.151]